Aprendizagem significativa aplicada ao ensino de conservação de energia mecânica - SANTOS, Sérgio Luiz Rodrigues (2024)
Considering that significant learning has relevant advantages compared to traditional method, in which the teacher exposes the content in a theoretical and repetitive manner, and being to the conservation of mechanical energy as central theme of Physics worked in high school, in order to relate this methodology to the proposed content, besides using the application Plickers as a voting system. There for, it is necessary to describe the conditions for the conservation of energy refer, to explain the main concepts of the theory of meaningful learning, to describe the main features of the Plickers application and to apply method for conservation content using the application as a system voting. Therefore, this work aimed to apply to the theory of meaningful learning in four class hours to the first-year high school class of the Vilhena Alves School. The theoretical framework is based on David Ausubel's theory of classical meaningful learning according reading or rereading to the teacher Marco Antonio Moreira, also on the physical theory of mechanical energy and its conservation written by teacher Renato Brito Basto Neto, as well as a brief research related to Plickers app and its classroom applications, so that, the analysis of the results obtained indicated that the strategies adopted in the method are efficient to the teaching of the conservation of the mechanical energy.